Identification and quantification of antioxidant compounds in cowpea - Moreira-Araújo, Regilda; Sampaio, Geni; Soares, Rosana Aparecida; Silva, Cintia; Arêas, José Alfredo (Revista Ciência Agronômica, 2017)
Dietary antioxidant compounds have been widely studied because of their ability to delay or inhibit oxidative damage, which allows them to play an important role in the prevention of diseases and the promotion of health. The identification and characterization of such compounds are required before their use in humans. This study aimed to identify and quantify antioxidant compounds in the cowpea cultivar, BRS Tumucumaque, and the cowpea strain, Pingo de Ouro 1-2, in view of their potential use in the development of new products with potent antioxidant activity. Here, we report the antioxidant activity and the phenolic compound content of the aforementioned cowpeas. The antioxidant extracts were analyzed by HPLC in a Shimadzu LC-20AT chromatograph model equipped with a manual injector using standard solutions of pure phenolic compounds, including gallic acid, quercetin, caffeic acid, chlorogenic acid, ferulic acid, p-coumaric acid, catechin, and epicatechin. Gallic acid was the phenolic compound with the highest level in both BRS Tumucumaque and Pingo de Ouro 1-2 (45.4 ± 2.66 and 93.4 ± 1.25 mg/100 g, respectively). Moreover, we identified and quantified catechin (5.67 ± 0.34 and 6.48 ± 0.51 mg/100 g, respectively), epicatechin (8.67 ± 0.47 and 2.95 ± 0.17 mg/100 g, respectively), ferulic acid (11.1 ± 1.42 and 13.8 ± 0.55 mg/100 g, respectively), and chlorogenic acid (2.39 ± 0.24 and 0.59 ± 0.28 mg/100 g, respectively). In contrast, caffeic acid was only identified in BRS Tumucumaque and quantified at 27.8 ± 2.99 mg/100 g. We conclude that Vigna unguiculata demonstrates functional potential, as both the strain and the cultivar contain antioxidant compounds that help in disease prevention and health maintenance.